Desertification Control Bulletin Number 32, 1998: A Bulletin of World Events in the Control of Desertification Restoration of Degraded Lands and Reforestation - United Nations Environment Programme (2019)
In this issue: Fourth Regional Meeting for Latin America and the Caribbean on the United Nations Convention to Combat Desertification; Application of Desertification Assessment Methodology for Soil Degradation Mapping in the Kalmyk Republic of the Russian Federation; Biodiversity Conservation, Conflict and Migration in Africa's Drylands: Linkages and Solutions; Desertification in Iceland; Agro-medicine Forestry: A New Land Use Production System for Arid and Semi-arid Regions of the Thar Desert; Rangeland Conditions and Animal Production Systems in Pakistan; Land and Water Resources and their Degradation in the Island of Crete, Greece; Water Resources in Yemen and their Degradation: the Risk for an Extensive Desertification; Afforestation and Social Forestry in Northern Nigeria: a Success Story in Desertification/Land Degradation Control; São João Baptista Valley Project, Cape Verde: A Success Story in Desertification/Land Degradation; etc.